PILOT STUDY OF LOWER UTERINE SEGMENT CESAREAN SCAR THICKNESS PREOPERATIVELY BY TRANSVAGINAL SONOGRAPHY AND ITS CORRELATION WITH INTRA-OPERATIVE FINDINGS - NAVDEEP KAUR; MANJIT MOHI; SARABJIT KAUR; SARYU GUPTA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Cesarean section rates are increasing with a decrease in the rate of trial of labor after first cesarean section. Proper assessment of uterus especially scar of the previous lower segment cesarean sections (LSCS) in pregnant females is the key stone for the successful vaginal birth after cesarean section. The objective of this pilot study was to evaluate LSCS scar thickness using transvaginal sonography (TVS) and to determine the correlation between TVS and intraoperatively measured lower uterine segment cesarean scar thickness. Methods: This prospective observational analytic pilot study was carried out jointly by the Departments of Obstetrics and Gynaecology and Radiodiagnosis, Government Medical College and Rajindra Hospital, Patiala after due ethical and research committee approval. 100 women at term with history of previous LSCS and who were scheduled for elective LSCS were recruited for the study after taking the informed consent. Pre-operative scar measurement as on TVS was compared with and analyzed with intraoperative (I/o) scar measurements taken by Calipers. Results: The cutoff value for TVS readings was found to be ≤2.5 mm using receiver operating characteristic analysis. It has significant correlation with I/o scar measurements. It also has a significant relationship with age, pre-pregnancy overweight, number of the previous LSCS, and gestational age. Conclusion: Assessment of the scar integrity and quality by TVS will be helpful in selecting candidates for trial of labor with an optimally informed decision but still a number of studies have to be done to develop a robust scoring system.